INDUKSI PEMBUNGAAN Mucuna bracteata MENGGUNAKAN PAKLOBUTRAZOL DENGAN SISTEM TANAM VERTIKAL: Flowering Induction of Mucuna bracteata through Paklobutrazol with Verticulture Culture - Sitanggang, Kamsia Dorliana; Hartati Yusida Saragih, Siti; Rizal, Khairul (Viabel : Jurnal Ilmiah Ilmu-Ilmu Pertanian, 2020)
Mucuna bracteata one of Legume Cover Crop many used in plantation. Mucuna bracteata can not flowering naturally. The objective of this research is to induce flowering Mucuna bracteata through paclobutrazol treatment with verticulture system. The methods are : induce shortly vegetative fase,count of secondary adventif shoot, count rise of flower,count number of flower and number of flower induced. Design of this research is Random block design 1 factor 4 treatment and 3 replication. The concentration of paclobutrazol are 0, 400, 500, and 600 ppm. The result show paclobutrazol 600 ppm able to suppress growth of main spiraling shoot increased 13,32 cm. The average number of secondary spiraling shoot are 3,84; 3,66 and 3,33.